Public Procurement–Intangible Investment Nexus: Insights into Endogenous Growth in Côte d’Ivoire - Ninquassau V.A. Koassi; Rebecca K. Yeo; Aymar G. Allangba; Eugene A. Kamalan (European Scientific Journal, ESJ, 2026)
Public procurement is increasingly recognized as a catalyst for economic growth, yet empirical research has largely focused on physical infrastructure investments. Far less attention has been paid to service-oriented public procurement, despite its potential to enhance knowledge accumulation, organizational capacity, and productivity. This study examines the growth effects of public service procurement in Côte d’Ivoire using an autoregressive distributed lag-error correction model (ARDL-ECM) applied to annual data from 1993 to 2024. Drawing on data from the General Directorate of Public Procurement (DGMP), the World Development Indicators (WDI), and the Central Bank of West African States (BCEAO), the analysis controls for private investment, public debt, industrial value added, trade openness, and inflation. The results indicate that public service procurement is a significant driver of long-run economic growth: a 10% increase in service procurement expenditure raises real GDP per capita by approximately 0.41%, despite the relatively small share of procurement in GDP. Short-run dynamics also reveal a positive immediate effect (0.34%), followed by gradual adjustment toward the long-run equilibrium. In contrast, gross fixed capital formation exhibits a negative long-run impact, pointing to structural inefficiencies in private investment, while industrial value-added supports growth and excessive debt accumulation constrains sustainability. These findings are consistent with endogenous growth theories emphasizing the role of intangible investments and extend the public finance literature beyond infrastructure-centric perspectives. Policy implications suggest that reorienting public procurement toward knowledge-intensive services could strengthen institutional capacity, foster innovation, and support sustainable growth in Côte d’Ivoire.